2018
DOI: 10.1042/bsr20181416
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme kinetics from circular dichroism of insulin reveals mechanistic insights into the regulation of insulin-degrading enzyme

Abstract: Insulin-degrading enzyme (IDE) is a zinc metalloprotease that selectively degrades biologically important substrates associated with type 2 diabetes and Alzheimer’s disease (AD). As such, IDE is an attractive target for therapeutic innovations. A major requirement is an understanding of how other molecules present in cells regulate the activity of the enzyme toward insulin, IDE’s most important physiologically relevant substrate. Previous kinetic studies of the IDE-dependent degradation of insulin in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(41 citation statements)
references
References 45 publications
4
37
0
Order By: Relevance
“…The bacterial expression vector encoding IDE fused to GST was kindly provided by Dr. Malcolm A. Leissring of the University of California at Irvine. GST-IDE was overexpressed in E. coli BL21-CodonPlus RIL cells (EMD Biosciences Inc., San Diego, CA, USA), and purified as previously described [ 25 , 26 , 27 ]. Cleavage of the GST tag was accomplished using GST PreScission protease and further purification of IDE was accomplished by standard gel filtration [ 25 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bacterial expression vector encoding IDE fused to GST was kindly provided by Dr. Malcolm A. Leissring of the University of California at Irvine. GST-IDE was overexpressed in E. coli BL21-CodonPlus RIL cells (EMD Biosciences Inc., San Diego, CA, USA), and purified as previously described [ 25 , 26 , 27 ]. Cleavage of the GST tag was accomplished using GST PreScission protease and further purification of IDE was accomplished by standard gel filtration [ 25 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…GST-IDE was overexpressed in E. coli BL21-CodonPlus RIL cells (EMD Biosciences Inc., San Diego, CA, USA), and purified as previously described [ 25 , 26 , 27 ]. Cleavage of the GST tag was accomplished using GST PreScission protease and further purification of IDE was accomplished by standard gel filtration [ 25 , 26 , 27 ]. UV absorbance at 280 nm was used to determine the concentration of IDE using an extinction coefficient of ε 280nm = 113,570 M −1 cm −1 [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, ATP and other nucleoside polyphosphates, as well as polyphosphate alone, induce dose-dependent allosteric inhibition of insulin degradation and, concomitantly, activation of short fluorogenic peptide substrates at physiologically relevant concentrations (1–5 mM) [ 50 , 183 ]. Interestingly, the activating effect is stronger for nucleoside triphosphates than nucleoside di- or monophosphates, and is attenuated in the presence of Mg 2+ [ 50 , 184 ]. Polyphosphate binding has been shown to occur at a specific region within IDE, known as the polyanion-binding domain [ 144 ], and appears to mediate activation of the protease towards short substrates by facilitating the transition from the closed state to the open conformation [ 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the effort in these studies has been directed toward investigating the impact of diffusion in fractal media on the reaction kinetics (22), with little focus on characterizing the effect of crowding on the mean effective enzyme kinetics. However, because it has now been shown that in vitro, some enzymes might not be limited by their translational diffusion but by their apparent association rate constants (24)(25)(26)(27)(28), the reevaluation of crowding in these reactions is important. In this work, therefore, we introduced computational methods for studying spatial effects of any kind, applying our work to the effects of crowding on reaction-limited enzymes with the goal of bridging the discrepancy between the in vitro measurement of kinetic parameters and the actual in vivo conditions.…”
Section: Introductionmentioning
confidence: 99%